Characteristic of migration in culture of newborn and fetal rat neural cells - Vsevolodska, Svitlana; Sukach, Oleksandr; Ochenashko, Olga (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):306